HUBUNGAN KEPEMIMPINAN DAN MOTIVASI DENGAN KINERJA KARYAWAN PADA PT. CARDOXINDO INTERBUANA - Hutasoit, SE., MSi., MSE, Posma Sariguna Johnson Kennedy; Santoso, Rahmat (Universitas Kristen Indonesia, 2016)
Leadership is an important element in a company, because in the absence of leadership from a leader so the company will suffer at set back. Basically of every leader has a different behavior in the lead. Or offen call of leadership. Leadership which is run by a leader in infiuencing the behavior of other in accordance with his wishes was fiuenced by the nature of the leader. Leaders with the good leadership will create high motivation within each subordinate, so that with motivation will a rise morale can improve the performance of subordinates.The purpose of this study is to know the relationship of leadership and motivation with employee perfomance on PT. Cardoxindo Interbuana. This research is descriptive – korelasional with up to to 30 people/responden and data were analyzed using analysis Rank Spearman and analysis multivariat Pearson Product Moment.The results showed that (1) There is a significant relationship between the leadership employee performance PT. Cardoxindo Interbuana with Rank Spearman correlation coeffcient of 0,831 which means the relationship between the two variabels is quite strong and is positive. (2) There is a significant relationship between motivation and employee performance PT. Cardoxindo Interbuana with Rank Spearman correlation coefficient of 0,845 so that is better the motivation that is created also increase the performance of employees, which means the relationship between the two variable is strong and positive value. (3) There is a significant relationship between the leadership and motivation of employee performance PT. Cardoxindo Interbuana with Pearson Product Moment correlation coeffcient of 0,877. The third variable which means the relationship is strong and positive. The analysis showed that leadership have a positive relationship to employee performance. The motivation was positively related to employee performance. With three variable that have a positive relation.Keywords: leadership, motivation and employees performance.